ANALYSIS OF STUDENT’S ABILITY IN WRITING NARRATIVE TEXT - Muhammad Hudri (Linguistics and ELT Journal, 2015)
This study aims at observing the students’ ability in writing narrative text at the second year of MTs Nurul Jannah NW Ampenan in Academic Year 2015/2016. Of 40 students, 20 students were chosen as the sample. The method used in this study was descriptive research. The data were collected through observation and writing test. It was found that the ability of the students in writing narrative text was on fair category. Based on the result, 10 students (50%) got score 56 - 65 (fair), 5 students (25%) got score 0 - 45 (very poor), 3 students (15%) got score 66 - 79 (good), and 2 students (10%) got score 46 - 55 (poor). Almost of all students are in between 56 - 65 (fair category). Meanwhile, Having analyze the students’ ability in each of writing aspects, it can be said that they were in inadequate category because most of them were inadequate in content. In other words, it means that they have very limited of ideas. The problems faced by the students were they made too much grammatical and spelling errors, difficulties in using connectors, and they have limited vocabulary and unable to select the appropriate diction.